Othello new perspectives (Victoria : Learning Essentials, 2000)
Summary: This program offers a close study of the relationships of Othello, lago and Desdomona, and attemps to define the nature of Othello's tragedy. Special attention is given to the situation of the women on the play. It indicates a range of possible interpretations of Othello on stage.
Presenter: Alan Dilnot, Sue Fweng
Keywords: Shakespeare, William, -- 1564-1616